2013
DOI: 10.4028/www.scientific.net/amr.813.298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca<sup>2+</sup> and Mg<sup>2+</sup> on Floatability of Smithsonite and Hemimorphite

Abstract: In this paper the effects of Ca2+ and Mg2+ on the floatability of smithsonite and hemimorphite were investigated through microflotation. The flotation tests were performed using purified samples from Lanping mine of China by the microflotation technique. The Ca2+ flotation results showed that the recovery of smithsonite decreased from 89.81% to 83.92% and the recovery of hemimorphite decreased from 84.83% to 76.03% when increasing Ca2+ concentration from 200mg/L to 1000mg/L. Also, while increasing Mg2+ concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Fang et al (2019) found that the recovery of diaspore hardly changed with the increase of Ca 2+ concentration, while Mg 2+ had a significant inhibitory effect. Li et al (2013) demonstrated that Mg 2+ had a greater inhibition on the smithsonite flotation. Different from the above views, Araújo and Lima (2017) discovered that Ca 2+ causes the smithsonite to be strongly inhibited instead of Mg 2+ in the smithsonite flotation.…”
Section: Introductionmentioning
confidence: 94%
“…Fang et al (2019) found that the recovery of diaspore hardly changed with the increase of Ca 2+ concentration, while Mg 2+ had a significant inhibitory effect. Li et al (2013) demonstrated that Mg 2+ had a greater inhibition on the smithsonite flotation. Different from the above views, Araújo and Lima (2017) discovered that Ca 2+ causes the smithsonite to be strongly inhibited instead of Mg 2+ in the smithsonite flotation.…”
Section: Introductionmentioning
confidence: 94%
“…However, the flotation of hemimorphite and smithsonite is relatively difficult due to their poor floatability [9]. Most of the existing studies mainly focus on the sulfidization-amine flotation process, i.e., sulfidization using sodium sulfide as the sulfurizing agent and using amine as the collector [10,11]. However, the separation efficiency of the sulfidization-amine flotation process is relatively low, and there are still some problems such as low selectivity of collector, low concentrate grade and the harmful impact of slime and dissolved ions on the flotation process.…”
Section: Introductionmentioning
confidence: 99%